Fuzzy logic model for prediction of mechanical properties of lightweight concrete exposed to high temperature - Tanyildizi, Harun (Elsevier Sci Ltd, 2009)
In this study, a fuzzy logic prediction model for compressive and splitting tensile strength of lightweight concrete made with scoria aggregate and fly ash after exposed to high temperature was devised. Cement dosages (400 and 500 kg/m(3)) were used in this study. The mixes incorporating 0%, 10%, 20% and 30% of fly ash were prepared. After being heated to temperatures of 200, 400 and 800 degrees C, respectively, the compressive and splitting tensile strength of lightweight concrete was tested. The obtained results with fuzzy logic were compared with the experimental methods and found remarkably close to each other. The results show that the fuzzy logic can be used to predict the compressive and splitting tensile strength of lightweight concrete after exposed to high temperature. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Ceramic matrix; Concrete; Mechanical